2020
DOI: 10.1002/cphc.202000177
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Dynamics of Zinc Triggers the Rate Determining Proton Transfer in Human Carbonic Anhydrase II

Abstract: We present, for the first time, how transient changes in the coordination number of zinc ion affects the rate determining step in the enzyme human carbonic anhydrase (HCA) II. The latter involves an intramolecular proton transfer between a zinc‐bound water and a distant histidine residue (His‐64). In the absence of time‐resolved experiments, results from classical and QM‐MM molecular dynamics and transition path sampling simulations are presented. The catalytic zinc ion is found to be present in two possible c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 121 publications
0
19
1
Order By: Relevance
“…In an attempt to simplify such a mapping task, we proposed in our earlier study , a method to identify potential CVs from a transition path ensemble and to find an optimum reaction coordinate, r , as a linear combination of a selected few of these CVs using machine learning based methods. It was also shown that when applied to a realistic system, the free energies and kinetics estimated along the optimum r could reproduce the experimentally observed values quantitatively. ,, In this article, we first demonstrate how to go beyond a linear approximation and construct nonlinear combinations of CVs using an artificial neural network (ANN) and derive an optimum reaction coordinate for a given enzyme catalyzed reaction. We further take up the challenge to show if the time scale of the process of interest may still be reproduced in agreement with experimental values.…”
Section: Introductionmentioning
confidence: 98%
“…In an attempt to simplify such a mapping task, we proposed in our earlier study , a method to identify potential CVs from a transition path ensemble and to find an optimum reaction coordinate, r , as a linear combination of a selected few of these CVs using machine learning based methods. It was also shown that when applied to a realistic system, the free energies and kinetics estimated along the optimum r could reproduce the experimentally observed values quantitatively. ,, In this article, we first demonstrate how to go beyond a linear approximation and construct nonlinear combinations of CVs using an artificial neural network (ANN) and derive an optimum reaction coordinate for a given enzyme catalyzed reaction. We further take up the challenge to show if the time scale of the process of interest may still be reproduced in agreement with experimental values.…”
Section: Introductionmentioning
confidence: 98%
“…This results in the polarization of the O–H bond of the zinc-bound water molecule for its subsequent deprotonation. 18 In addition, dynamical fluctuations of the unprotonated His-64 side-chain ensure that it is predominantly orientated inward, facing the zinc ion, ready to accept the excess proton. The associated rate constants are estimated to be k reorg ≈ 10 7 –10 9 s –1 as shown in Figure 1 d. 12 , 14 16 , 18 , 20 …”
Section: Introductionmentioning
confidence: 99%
“…We note that the method of hybrid QM/MM calculations has been used in many earlier works to study the mechanism and energetics of several different enzymatic reactions. , However, to the best of our knowledge, such a study of the mechanism and free energy landscape of the transimination reaction of the PLP-SHMT complex in the presence of serine considering the full structural details of the enzyme, PLP, substrate, and surrounding environment is presented here for the first time. Given that the transimination process is a required pre-step for exhibiting the enzymatic activity of a PLP-dependent enzyme like SHMT, it is indeed important to have an understanding of the free energetics and reaction pathways of this process at molecular level.…”
Section: Introductionmentioning
confidence: 99%